2009
DOI: 10.1592/phco.29.12.1433
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Drug Use and Hospitalization Rates in Patients Undergoing Hemodialysis Who Received Pharmaceutical Care: A 2‐Year, Randomized, Controlled Study

Abstract: Identification and resolution of DRPs through pharmaceutical care resulted in decreased drug use and costs for patients undergoing hemodialysis. Hospitalization rates were significantly lower in the pharmaceutical care group, with a trend toward shorter duration. Provision of pharmaceutical care is associated with tangible benefits on outcomes in ambulatory patients undergoing hemodialysis and should be considered in health care policy decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 11 publications
0
64
0
Order By: Relevance
“…This result suggests that more than 70% of MRPs could be addressed by systematic MTM at the dialysis facility during routine care and at transition back to the dialysis facility, potentially preventing readmission. In a 2-year randomized, controlled trial of 104 hemodialysis patients assigned to receive pharmaceutical care (in-depth bimonthly medication therapy reviews conducted by a clinical pharmacist) or usual care (brief medication therapy reviews conducted by nurse), the former was associated with fewer hospitalizations (1.862.4 versus 3.163, P50.02); the trend for reduced lengths of stay did not achieve statistical significance (9.7614.7 versus 15.5616.3 days, P50.06) (11). A recent study showed that integrated pharmacy services in hemodialysis patients receiving Medicare and Medicaid were associated with lower rates of death and hospitalization (35).…”
Section: Significant Total Cost Of Care Savings Could Be Realized Thrmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that more than 70% of MRPs could be addressed by systematic MTM at the dialysis facility during routine care and at transition back to the dialysis facility, potentially preventing readmission. In a 2-year randomized, controlled trial of 104 hemodialysis patients assigned to receive pharmaceutical care (in-depth bimonthly medication therapy reviews conducted by a clinical pharmacist) or usual care (brief medication therapy reviews conducted by nurse), the former was associated with fewer hospitalizations (1.862.4 versus 3.163, P50.02); the trend for reduced lengths of stay did not achieve statistical significance (9.7614.7 versus 15.5616.3 days, P50.06) (11). A recent study showed that integrated pharmacy services in hemodialysis patients receiving Medicare and Medicaid were associated with lower rates of death and hospitalization (35).…”
Section: Significant Total Cost Of Care Savings Could Be Realized Thrmentioning
confidence: 99%
“…Not surprisingly, several studies have shown a high prevalence rate of MRPs in patients undergoing maintenance dialysis (6,(10)(11)(12) (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality is increased on the first day back after the long interdialytic interval of the weekend, 7 which fueled the suggestion that more frequent treatments with narrower shifts in…”
Section: Disclosuresmentioning
confidence: 99%
“…The involvement of pharmacists has been shown to not only identify actual and potential MRPs, but to reduce rehospitalizations and lengths of stay of dialysis patients. 7,8 In another common scenario, the ESRD patient is admitted for an infectious cause or sepsis, receives appropriate intravenous antibiotics after positive wound or blood cultures, and is discharged as soon as clinical symptoms improve, with the presumption that the same antibiotic regimen can be continued in the dialysis unit. Unfortunately, in many cases, the information about the specific intravenous antibiotic is not transmitted to the dialysis facility in time for the facility to order the antibiotics.…”
mentioning
confidence: 99%
“…Most of the pharmacist interventions involved medication profile reviews to address drug-related problems such as dosage adjustments related to renal function, making recommendations to the physicians, adjusting medications to optimize drug therapy, performing laboratory monitoring of specific parameters, and medication education. In a 2-year randomized controlled study [31] of patients undergoing hemodialysis, the intervention group involved in-depth one-on-one drug reviews with a pharmacist. This group compared to usual care contributed to a significant average reduction in all-cause hospitalizations.…”
Section: Evidence Supporting Improved Cardiovascular and Kidney Outcomentioning
confidence: 99%